1994
DOI: 10.1007/bf02451656
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of metastable H(2S) atom by electron and positron impact

Abstract: Summary. --Triple differential cross-section (TDCS) of hydrogen atom in its metastable (2S) state is studied theoretically by electron and positron impact for coplanar and asymmetric geometry. The final-state wave function in the present model satisfies the asymptotic boundary condition for asymmetric geometry (i.e. for k 1 >> kz). In the absence of experiment, present results are compared with other existing theoretical results. Apart from the double-peaked structure of the TDCS as in ground-state ionization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In view of all of these, quite a few theoretical and experimental studies were reported for the electron [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and photon [26][27][28][29] impact collisions of metastable atoms, although there are relatively fewer experiments. The main reason for the scarcity of the experimental data is possibly the difficulty in generating these species in the relatively high concentrations necessary for collisional cross section measurements [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of all of these, quite a few theoretical and experimental studies were reported for the electron [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and photon [26][27][28][29] impact collisions of metastable atoms, although there are relatively fewer experiments. The main reason for the scarcity of the experimental data is possibly the difficulty in generating these species in the relatively high concentrations necessary for collisional cross section measurements [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the fully triple differential cross sections (TDCS) for the (e, 2e) process were widely studied for the ground-state H atom in the field-free (FF) situations, both experimentally [30][31][32][33][34] and theoretically [35][36][37][38][39], while for the ionization from the metastable state (of H atom) no such TDCS measurement is yet available in the literature, although the absolute total cross sections (TCS) were measured much earlier [12,13]. However, on the theoretical side, quite a few calculations on the TDCS of the metastable (2S) hydrogen atom using electron impact were performed for the FF situation [14][15][16][17][18][19][20][21][22]. Significant differences were noted [21] in the TDCS structures when compared to the ground-state ionization cross section and some new features were found in the metastable case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the fully triple differential cross sections (TDCS) for the (e, 2e) process have been extensively studied for the ground state hydrogen atom both theoretically and experimentally, while for the ionization from the metastable state no such measurement of TDCS is yet available in the literature, although the absolute total cross sections have been measured much earlier [3,4]. However, on the theoretical side, quite a few calculations have been performed on the TDCS of the metastable (2S) hydrogen atom using electron impact [5][6][7][8][9][10][11] and significant differences were observed in the TDCS structures when compared to the cross section of ground-state ionization. All these theoretical calculations available in the literature to date have been done within the framework of the asymmetric geometry and at low energies.…”
mentioning
confidence: 99%
“…Figure(9) also shows that for all figures in the symmetric geometry, in which we choose φ B to be constant, it must be equal to 180 • since the pick is clearly located at the same value. Figure(10) represents the variations of TDCS in the RPWBA in terms of the scattered and ejected electron angles at the energies T i = 5000 eV and T B = 2498.3 eV. The purpose of including this figure is to show how important the condition on both angles to be verified in the symmetric coplanar geometry.…”
mentioning
confidence: 99%